Development of Teaching Materials for French Courses for Class X SMA Based on 2013 Curriculum Using Instagram Media - Evi Eviyanti; Irwandy; Rabiah Adawi (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
In the 21st century the learning process must integrate Information and Communication Technology (ICT) in learning activities. The development of information and communication technology causes the need for learning to also grow rapidly and the concept of learning can be implemented with the help of technology such as the internet. In 2020, internet-based learning activities have been widely implemented in the field of education, from elementary to university levels due to the Covid-19 pandemic in the world. This condition requires physical distancing to break the chain of the spread of Covid-19. All schools and colleges responded by carrying out learning from home, through online learning with the use of information technology. The purpose of this research is to: (1) develop teaching materials for French class X high school based curriculum 2013 using Instagram media, (2) assess the feasibility of teaching materials for French class X high school based curriculum 2013 using Instagram media, and (3) explain the effectiveness of the materials teach French class X subjects in high school based on the 2013 curriculum using Instagram media. This development research uses the ADDIE development model (Analysis, Design, Development, Implementation, Evaluation). The research instrument used was a questionnaire and a written test. The product of research results (teaching materials for French class X SMA subjects must be validated by experts before being tested in the field (experiments).